The benefits of being dominant: health correlates of male social rank and age in a marmot. Issue 1 (28th April 2021) - Uchida, Kenta; Ng, Rachel; Vydro, Samuel A; Smith, Jennifer E; Blumstein, Daniel T
Abstract: The benefits of dominance may not come without costs, particularly for males. For example, the "immunocompetence handicap hypothesis" states that males with enhanced mating success allocate resources to enhance reproductive output at a cost to their current health, whereas the "resource quality hypothesis" predicts that high-ranking males may benefit from increased reproduction and good health. Whereas the predictions from each have been well tested in captive animals and in a variety of highly social primates, fewer studies have been carried out in free-living, facultatively social animals. Using adult male yellow-bellied marmots ( Marmota flaviventer ), we evaluated predictions of these hypotheses by examining the relationship between social rank and 2 health indicators—fecal glucocorticoid metabolite (FCM) levels, and neutrophil/lymphocyte (N/L) ratios—after accounting for variation explained by age, body mass, and seasonality. We found that higher-ranking males tended to have a lower N/L ratio (reflecting good health) than lower-ranking individuals, whereas FCM levels were not significantly related to rank. In addition, heavier male marmots had lower N/L ratios, whereas body mass was not associated with FCM levels. We also found that older adult males had lower FCM levels (reflecting less physiological stress) but higher N/L ratios than younger adults. Finally, we found that FCM levels decreased as the active season progressed and FCM levels were associated with the time of the day. Overall, our results suggest that socially-dominant male marmots enjoyed better, not worse health in terms of lower N/L ratios.